The Development of Elderly Care Management Model of Local Administration Organization in Nonthaburi, Thailand - Monnuanprang, Piangpob; Vanpetch, Wichai; Sangngern, Supot; Maneechote, Tiwat; Chuaypanang, Kasem; Chodilok, Sunee (Asian Interdisciplinary and Sustainability Review, 2019)
The purposes of this research were to study general condition, development model and evaluation of elderly care management model. This research adopted mix methods: quantitative and qualitative and the participatory action of collecting data from government organization and private organization. The research instruments which adopted questionnaire, interview form, observation and people forum. The quantitative data was analyzed by percentage, mean, standard deviation and the qualitative data was analyzed by content analysis. The research result showed as follow: 1) the general condition of elderly showed that they were living alone. They need supporting in health care and some of them were depression and self-reliance. The elderly need support from community and society in facilities of traveling, living place for homeless, suitable job for elderly, supporting funds and getting into government service. 2) Elderly care management model consists in 6 parts: planning, staff working management, directing, cooperating, working and reporting and budget. 3) The result of elderly care management model showed that before planning of staff working management, directing, cooperating, working result report and budget are in middle level but after using the model all parts are in high level. 4) The evaluation of elderly care management model as the quality assurance in planning is at high level, staff working management is at high level, directing is at high level, cooperating is at high level, working result report is at the highest level and budget is at the highest level.